Hepatomegaly due to self-induced hyperinsulinism. Issue 2 (February 1979) - Asherov, J; Mimouni, M; Varsano, I; Lubin, E; Laron, Z
Abstract : Repeated hypoglycaemic attacks, associated with transient hepatomegaly, in a 12-year-old insulin-dependent diabetic girl continued despite reduction in dose and, later, complete discontinuance of insulin. The attacks ceased while she was in hospital, necessitating reinstitution of insulin. The hepatomegaly resolved when surreptitious additional insulin injections were discovered and stopped. Hepatomegaly in diabetics should arouse suspicion of overdosage with insulin.